Anorectal disorders : diagnosis and non-surgical treatments - Coss-Adame, Enrique; Troche-Remes, Jose M. (Academic Press, 2019)
Anorectal Disorders: Diagnosis and Nonsurgical Treatments incorporates the most recent major advances in the understanding of anal and rectal anatomy to provide clinical evidence of care for those suffering from anorectal disorders. By condensing basic and practical aspects in the knowledge of anorectal disorders, this book provides a comprehensive review of the anatomy and physiology of the anorectal region. It includes new technology that expands and modifies current perceptions about the functional anatomy of the anorectal region and ultimately impacts how we conceive muscle and nerve structures functioning together to maintain fecal continence and properly execute the process of defecation. Perfect for medical researchers, gastroenterologists, general practitioners, internal medicine doctors and general surgeons, this title will provide diagnosis and treatment options for all patients suffering from anorectal disorders.